Fair Use for Nonfiction Authors Common Scenarios with Guidance from Community Practice - Walker, Robert Kirk (Authors Alliance, 2017)
The Authors Alliance guide to Fair Use for Nonfiction Authors is designed to empower authors to exercise their right to use source materials to further their research and writing goals by helping them to make confident fair use decisions. The guide addresses three common situations faced by nonfiction authors in which fair use may apply: 1) criticizing, discussing, or commenting on copyrighted material; 2) using copyrighted material to support a point made in the author's work; and 3) using copyrighted material for non-consumptive research. It also addresses the most frequently asked questions about fair use and clears up some common misconceptions about when it might apply.